Analisis Pengaruh Tingkat Kesehatan Bank dengan Menggunakan Metode CAMEL terhadap Profitabilitas pada Sektor Perbankan Periode 2017–2021 - Andika, Andika (Jurnal KIAFE, 2025)
This study examines the effects of bank soundness indicators based on the CAMEL method on profitability in banking-sector companies listed on the Indonesia Stock Exchange during the 2017–2021 period. The study employs a quantitative descriptive approach using secondary data obtained from annual financial statements. The sample was selected through purposive sampling and consisted of 23 banking companies, resulting in 115 firm-year observations. Bank profitability was measured using Return on Assets, while bank soundness was represented by the Capital Adequacy Ratio, Non-Performing Loan ratio, Net Interest Margin, Operating Expenses to Operating Income ratio, and Loan-to-Deposit Ratio. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS. The results show that Net Interest Margin has a positive and significant effect on Return on Assets, while Operating Expenses to Operating Income has a negative and significant effect. Capital Adequacy Ratio, Non-Performing Loan ratio, and Loan-to-Deposit Ratio do not have significant effects on Return on Assets. Simultaneously, the five CAMEL indicators significantly affect bank profitability. The adjusted coefficient of determination is 87.5%, indicating that the research model explains 87.5% of the variation in Return on Assets.